Topografía, escalas y casos: los tres tiempos de la Compañía de Jesús en Chile (1568-1626) - Rafael Gaune Corradi (Nuevo mundo - Mundos Nuevos, 2015)
The aim of this paper is reviewing my doctoral trayectory troughout a methodological and analytical reading. My interest has been focused on the political and religious mediation forms that the Jesuit Company used between Rome and Chile, from 1568 to 1626. I propuse consider the bonds between the local develop and the global dimension, conecting with the recent historiography about Global History. I have attached special importance to the concept topography.